Three-dimensional traction technology and its application in mechanomedicine - Xinman Chen; Chenyang Ji; Xi Liu; Ning Wang; Fuxiang Wei; Junwei Chen (Mechanobiology in Medicine)
Endogenous forces generated by living cells are essential for biological processes and physiological functions of cells and tissues. Over the last several decades, numerous methods for detecting traction forces have been developed. Here we review these methods and discuss their respective strengths and limitations. Being able to reliably quantify tractions in living cells and tissues are critical in understanding how forces drive and regulate cell and tissue functions in physiology and diseases.